Synthesis of zinc oxide and zinc oxide / iron oxide catalysts and their photocatalytic activity in degrading herbicides - Lee, Kian Mun (2013)
In this study, ZnO and ZnO/Fe2O3 catalysts were synthesized via precipitation method. The effect of Fe addition, calcination temperature and duration on the characteristics of the resulting catalyst were investigated by performing Thermogravimetric Analysis (TGA), X-ray Diffraction (XRD), Transmission Electron Microscopy (TEM), surface area measurement (BET method), Diffuse Reflectance Spectroscopy (DRS) and Inductively-coupled plasma atomic emission spectroscopy (ICP-AES). XRD analysis showed that the addition of Fe resulted in the formation of hexagonal structure of ZnO and cubic structure of γ-Fe2O3 by calcining the sample at 450 °C for one hour. The catalysts produced were spherical in shape. The increase in the calcination temperature and duration does not change the morphology and band gap energy of the resulting catalysts. However, the surface area of the catalyst decreased and hence leads to an increment in its particle size as the calcination temperature and duration increased. ICP-AES results revealed that the iron content in ZnO/γ-Fe2O3 is in good agreement with the calculated values. The efficiency of the synthesized ZnO/γ-Fe2O3 as photocatalysts was evaluated by photodegrading herbicides 2,4-dichlorophenoxyacetic acid (2,4-D), 2,4,5-trichlorophenoxyacetic acid (2,4,5-T), phenoxyacetic acid (PAA) and 4-chlorophenoxyacetic acid (4-CPA) under the irradiation of ultraviolet (UV, λmax = 365 nm) light. Various parameters affecting the degradation performance such as catalyst dosage, initial concentration of herbicides and initial pH were examined. The removal percentage of chlorophenoxyacetic acids increased with increasing mass of ZnO/γ-Fe2O3 up to an optimum loading (0.4 g L-1 for 2,4-D and 2,4,5-T with 66.07 and 68.16 %, respectively and 0.5 g L-1 for PAA and 4-CPA with 60.90 and 74.38 %, respectively) but decreased with increasing initial concentration (from 10 - 50 mg L-1) of the herbicides. The removal of chlorophenoxyacetic acids is highest at pH 7. The photodegradation of chlorophenoxyacetic acids followed first-order kinetic scheme. The intermediates detected by UPLC for 2,4-dichlorophenoxyacetic acid (2,4-D), 2,4,5-trichlorophenoxyacetic acid (2,4,5-T), phenoxyacetic acid (PAA) and 4-chlorophenoxyacetic acid (4-CPA) are 2,4-dichlorophenol, 2,4,5-trichlorophenol, phenol and 4-chlorophenol, respectively. Experimental design methodology was applied using response surface methodology (RSM) to optimise the degradation percentage of chlorophenoxyacetic acids. The multivariate experimental design was employed to develop a quadratic model as a functional relationship between the degradation percentage of chlorophenoxyacetic acids and catalyst dosage, initial concentration of herbicides and initial pH. The degradation percentage of 2,4-D approached 99.26 % under optimised conditions of 0.50 g ZnO/γ-Fe2O3, 10.00 mg L-1 2,4-D and at a pH of 7.49 whereas 2,4,5-T achieved 83.58 % under optimised conditions of 0.41 g ZnO/γ-Fe2O3, 10.60 mg L-1 2,4,5-T and at pH 7.11. The maximum removal percentage of PAA approached 76.43 % under optimised conditions of 0.51 g ZnO/γ-Fe2O3, 10.20 mg L-1 PAA and at pH 6.63. Further, 4-CPA showed maximum removal of 91.87 % under optimised conditions of 0.49 g ZnO/γ-Fe2O3, 10.10 mg L-1 4-CPA and at pH 7.25. In addition, the experimental data showed good agreement with the predicted results obtained from statistical analysis which indicates response surface methodology is applicable in optimising the degradation percentage of chlorophenoxyacetic acids.